Analysis Of Climate Change Based On Fishermen's Perception At Tpi Lempasing Teluk Betung Timur - Rifqi, Muhammad; Yuliawan, Dedy (MSJ : Majority Science Journal, 2024)
The aim of this research is to find out the impact of climate change on fishermen's income at TPI Lempasing Teluk Betung Timur.The research method used in this research is a field study with a qualitative approach, the data itself comes from primary and secondary data,, in the analysis process the stages of reduction, data display and conclusions are used. Based on the results of the analysis that has been carried out, it can be concluded that the impact of climate change in the Lempasing area of East Betung Bay has greatly influenced fishermen's income, which on average usually reaches between 2 million and 5 million per month. When bad weather strikes, such as frequent storms and increased extreme rainfall, fishermen are often unable to go to sea and receive no income at all. This causes significant economic uncertainty for them, with the possibility of facing difficulties in meeting their daily needs and maintaining the survival of their families.